The Development of Problem-Based Learning Management Model for Enhancing Academic Resilience of Pre-Service Teacher Students - Kambhu na ayudhaya, Paradee; Chularut, Pasana; Aeamtussana, Thammachot (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
This research aimed to 1) examine the construct validity of academic resilience measurement model of pre-service teacher students, 2) develop the problem-based learning management model to enhance the academic resilience of pre-service teacher students and 3) study the effect of the problem-based learning management model. The samples were divided into 2 groups: (1) The samples used to study the components of academic resilience were 595 undergraduate pre-service teacher students from public universities, autonomous universities, and Rajabhat Universities located in 4 regions of Thailand: the North, the Central, the Northeast, and the South (2) 26 undergraduate pre-service teacher students from Srinakharinwirot University who had the average academic resilience score below the 25th percentile down randomly selected as an experimental group and a control group, each of which had 13 participants. The research instruments were the academic resilience test with a reliability coefficient of .92 and the problem-based learning management model for enhancing academic resilience of pre-service teacher students. The data were analyzed by means, standard deviation, and t-test. The results showed that; 1) The academic resilience measurement model was consistent with the empirical data that standardized factor loading ranged from 0.76 to 0.93 with statistically significance at the .01 level for all components, 2) The problem-based learning management model to enhance academic resilience consisted of 5 steps. Step 1: Identify the problem Step 2: Understand the problem Step 3: Study and research Step 4: Consider the solution Step 5: Summarize and present the solution 3) after the experiment, the academic resilience score of the experimental group was higher than the control group and before the experiment with statistically significance at the .01 level.